Services Offshoring and Its Strategic Effects on Value Chains - Paulo Roberto Gião; Moacir de Miranda Oliveira Júnior; Eduardo Pinheiro Gondim de Vasconcellos (BAR: Brazilian Administration Review, 2008)
This article’s main objective is to examine some known management theories under the offshoring point of view. It detaches some factors in existing theories and how they can be at risk in an increasing offshoring of services processes. In the absence of more systematic studies about the effects of offshoring over value chain and core competencies imprecise borders and definitions, we try to interpret them in a holistic manner and stimulate discussions in a new area of study rather than to provide definitive general conclusions. The methodological aspects mainly concerning the offshoring bibliography are very impressive, especially since 2000. There seems to be a new trend appearing, like a wedge between strategy and international business theories, or that at least complements these theories. The analysis presented in this paper is offered as an aid to systematic investigation involving value chains, core competencies, innovations and the accelerated process of offshore outsourcing of services. Some preliminary evidence showed countries and companies in good conditions to improve their participation in the international market. The internationalization of these new firms from emerging countries and their learning process may need extension to existing theories, at least from the perspective of emerging and in the developing world.